GAMBARAN KEBUGARAN JASMANI MAHASISWA PENDIDIKAN OLAHRAGA FKIP UNRI SELAMA PANDEMI COVID-19 - S, Wedi; Saputro, Deny Pradana; Sinulingga, Andrew Rinaldi (Jurnal Sporta Saintika, 2021)
Having good physical fitness is one of the important elements that must be possessed by someone, especially sports students, because most of the study process is by doing physical activity. Meanwhile, during the Covid-19 pandemic, all study activities are carried out by online methods. This of course will result in a decrease in their physical fitness. This study aims to see and determine the Physical Fitness Level of sports coaching education students during the Covid-19 pandemic. This study uses a descriptive research method with a population and a sample of 38 people who are students of sports coaching education in semester 3. The data retrieval used in this study was an Indonesian Physical Fitness Test which consisted of several test items, namely: a 60 meter running speed test, a pull up test, a sit up test, an vertical jump test, and a 1200 meter run test. Data analysis used descriptive statistical analysis techniques with presentation in the form of percentages. The results showed that there were no students who had a very good physical fitness level, 3 students (7.89%) had a good physical fitness level, 20 students (52.63%) had a physical fitness level with Medium classification, 10 students (26.32%) have a level of physical fitness with a classification of Poor and 5 students (13.16%) have a level of physical fitness with a classification of Very Poor. Based on this data, the researcher can conclude that the Physical Fitness Level of the Sports Coaching Education Students at the Riau University during the COVID-19 Pandemic mostly fell into the Medium and Poor category, with a total of 20 people (52.63%) in the Medium Level category and 10 (26, 32%) People in the Poor Level category.